Defunctioning stoma in high-risk rectal anastomosis - Del Rio, P.; Dell'Abate, P.; Soliani, P.; Arcuri, et al., M F. (Acta Biomedica Atenei Parmensis, 2009)
Background: Ileostomy in rectal surgery is not always indicated for protecting the anastomosis. Methods: We examined patients who underwent low rectal resection surgery for carcinoma between June 2005 and December 2007. We categorized the patient’s characteristics according to the American Society of Anesthesiologists (ASA). We estimated hospital stay, and postoperative Dukes stage. Results: 68 patients, 47 males and 21 females (mean age 67.8 years, range 40-85 years) treated with low rectal resection for carcinoma. An ileostomy was performed in 29 out of 68 patients (42.6%). Six postoperative ileostomy cases led to the appearance of peritonitis from anastomotic fistula. Among the patients with ileostomy 19 pts. (65.5%) belonged to ASA II and 10 pts.(34.5%) to ASA III; among those patients without ileostomy, 32 (82.05%) ASA II and 7 (17.95%) ASA III (p=n.s.). Of patients who underwent the first protective surgical procedure, 4 belonged to ASA II (66.6%) and 2 to ASA III (33.3%). The mean hospital stay for the non ileostomy group was 7.64±0.7 days, while it was 7.36±0.49 (p=n.s.) for the ileostomy group.The mean stay of postoperative ileostomy for leakage was 10.83±1.16 days. Conclusions: Ileostomy cannot completely prevent the onset of leakage, but may reduce overall hospitalization time.